(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To examine trends in antibiotic utilization at Thu Duc City Hospital (TDCH) from January 2022 to June 2024. Materials and Methods: This cross-sectional, retrospective study leveraged electronic health records to analyze antibiotic costs for health insured patients at TDCH between January 2022 and June 2024. Trends in antibiotic utilization and associated treatment costs were assessed at 6-month intervals, categorized by antibiotic classes and average cost per prescription. Results: Over the study period, a total of 540,164 antibiotic prescriptions were recorded for insured patients at TDCH, of which 65.1% were for outpatients. The rate of antibiotic prescriptions varied from 17.4% to 19.2% for inpatients and from 6.1% to 7.2% for outpatients. Antibiotic expenses accounted for 54.6% (VND 38.491 billion) of total costs in inpatient care and 45.4% (VND 32.041 billion) in outpatient care. The proportion of antibiotic costs relative to total drug expenditure declined over time, from 26.5% to 22.3% in inpatient and from 9.5% to 5.6% in outpatient. Beta-lactams, Quinolones, and Nitroimidazoles were the most frequently prescribed antibiotic classes in both inpatient and outpatient care. Notably, the prescription rates and costs associated with Beta-lactams showed a downward trend across both settings. The average cost per antibiotic prescription decreased over time, from VND 218,000 to VND 186,000 for inpatients and from VND 142,000 to VND 77,000 for outpatients. Conclusion: The findings of this study provide valuable insights into antibiotic prescribing patterns and cost trends at TDCH from January 2022 to June 2024. These data offer a foundation for the hospital’s antibiotic stewardship efforts and inform future drug procurement strategies.